Menstrual Leave in the Workplace: Inequality in Implementation from a Liberal Feminist Perspective - Wulandari, Diva Agestin (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2026)
The inequality in the implementation of menstrual leave rights for women in the workplace in Indonesia remains a significant issue, despite being regulated under Law Number 13 of 2003 concerning Manpower. This study aims to analyze the factors contributing to this inequality and to examine the phenomenon through the lens of liberal feminist theory. This research employs a qualitative literature review method, collecting and analyzing data from various written sources, including books, journal articles, and research reports. The findings indicate that inequality in the implementation of menstrual leave rights is influenced by legal, cultural, economic, and internal company policy factors. The main obstacles include weak enforcement of regulations, social stigma surrounding menstruation, complicated administrative procedures, and a workplace culture that is not gender-sensitive. From a liberal feminist perspective, this inequality reflects the failure of both the state and companies to ensure equal rights and adequate protection for women workers. The implications of this inequality affect women’s health, well-being, and position in the workplace. This study recommends strengthening regulatory oversight, reforming company policies, and promoting education to eliminate menstrual stigma in order to create a fair and equitable working environment for women.